Impacts of recreational cannabis legalization on cannabis use: a longitudinal discordant twin study. (24th August 2022) - Zellers, Stephanie M.; Ross, J. Megan; Saunders, Gretchen R. B.; Ellingson, Jarrod M.; Anderson, Jacob E.; Corley, Robin P.; Iacono, William; Hewitt, John K.; Hopfer, Christian J.; McGue, Matt K.; Vrieze, Scott
Abstract: Aims: To estimate the effect of recreational legalization on cannabis use frequency and sources of variance across legal environments. Design: Longitudinal discordant twin and gene–environment interaction models in twins recruited from birth records and assessed prospectively. Setting: The United States, including states with different recreational cannabis policies before and after 2014, when recreational cannabis was first legalized. Participants: Two longitudinal, prospectively assessed samples of American twins aged 24–47 ( n  = 1425 in legal states, n  = 1996 in illegal states), including 111 monozygotic pairs discordant for residence. Measurements: Current cannabis use frequency (measured continuously and ordinally) was the primary outcome, and the predictor was recreational status of cannabis (legal/illegal) in the participant's state of residence at the time of assessment. Covariates include age, sex and cannabis use frequency prior to 2014. Findings: Accounting for pre‐2014 use, residents of legal states used cannabis more frequently than residents of illegal states ( b  = 0.21, P  = 8.08 × 10 −5 ). Comparing 111 pairs of monozygotic twins discordant for residence confirmed the effect ( b  = 0.18, P  = 0.014). There was inconclusive evidence for genetic influences on cannabis use frequency that were specific to the legal environment [χ 2  = 2.9 × 10 −9, degrees of freedom (d.f.) = 1, P  > 0.999]. Existing genetic influences were moderated by the legal environment, as the genetic correlation between marijuana use before and after legalization was lower in states that legalized ( r genetic  = 0.24) compared with states that did not ( r genetic  = 0.78, P difference  = 0.016). Conclusions: In the United States, there appears to be a ~ 20% average increase in cannabis use frequency attributable to recreational legalization, consistent across increasingly rigorous designs. In addition, the heritability of cannabis use frequency appears to be moderated by legalization.